Lipid packing defects are necessary and sufficient for membrane binding of α-synuclein - David H. Johnson; Orianna H. Kou; John M. White; Stephanie Y. Ramirez; Antonis Margaritakis; Peter J. Chung; Vance W. Jaeger; Wade F. Zeno (Communications Biology)
Abstract α-Synuclein (αSyn), an intrinsically disordered protein implicated in Parkinson’s disease, is thought to initiate aggregation by binding to cellular membranes. Previous studies suggest that anionic lipids are necessary for this binding. However, these studies largely focused on unmodified αSyn, while physiological αSyn is N-terminally acetylated (NTA). Our work challenges the long-standing paradigm that anionic lipids are necessary for αSyn binding by demonstrating that NTA diminishes αSyn’s reliance on anionic membranes, revealing that membrane packing defects (i.e., interfacial hydrophobicity) alone can drive membrane binding. Using fluorescence microscopy and circular dichroism spectroscopy, we monitored the binding of NTA-αSyn to membrane vesicles with different lipid compositions. Phosphatidylcholine and phosphatidylserine concentrations were varied to control surface charge, while phospholipid tail unsaturation and methylation were varied to modulate lipid packing. We also formulated cholesterol-containing membranes that mimicked the lipid composition of synaptic vesicles. In these membranes, all-atom molecular dynamics simulations were used to visualize and quantify membrane packing defects. Our results demonstrate that membrane packing defects are necessary for NTA-αSyn binding and that defect-rich membranes are sufficient for NTA-αSyn binding regardless of membrane charge. These findings provide a molecular mechanism by which lipid structural properties, such as poly-unsaturation, can regulate αSyn binding to physiological membranes.